A new genus and species of myrmecophile clearwing moth (Lepidoptera: Sesiidae) from East Africa - Agassiz, David; Kallies, Axel (Zootaxa, 2018)
A new genus, Osmanthedon Kallies gen. nov., in the tribe Synanthedonini and a new species, Osmanthedon domaticola Agassiz & Kallies spec. nov., are described. This is the first record of a sesiid species associated with ant galls (domatia) found on whistling thorn Acacia, Vachellia drepanolobium (Harms ex Sjöstedt) P.J.H.Hurter (Fabaceae), in East Africa.